No Place Like Home - Mary Higgins Clark (New York Pocket Books, Inc., 2006)
Growing up under an assumed identity after accidentally shooting her mother and escaping her abusive father, Liza Barton, still fearful that her past will reclaim her, is shocked when her husband inadvertently buys her childhood home
In the latest thriller from America's queen of suspense--available in this slim Premium Edition--a young woman is ensnared into returning to a place she had wanted to leave behind forever: her childhood home
Includes an excerpt from Two little girls in blue
Keywords: Literature (3GdCOHs; General -- Fiction; Violence in children; Mothers -- Death -- Fiction; Home ownership -- Fiction; Married women -- Fiction; Abused wives -- Fiction; Stepfathers -- Fiction